Plural Sovereignties and Contemporary Indigenous Literature - Christie, S. author. aut Link
XIV, 280 p.
Keywords: Offering close readings of novels by Sherman Alexie to Leslie Marmon Silko, this book documents the reinvention of Anglo-European nationality in the interests of sustaining the indigenous traditions that long-preceded colonization.